Pengembangan Blended Learning Berbasis Dynamic Intelectual Learning pada Mata Pelajaran Biologi Kelas X MA Mambaul Ulum Solokuro Tahun Ajaran 2017/2017 - Kholifatur Rosyidah; Lilik Mawartiningsih (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This reseacrch is based on the researcher’s desire to know the ability of MA Mambaul Ulum students in using blended learning based on dynamic intellectual  learning on the subjeccts of Biology class X of academic year 2017/2018. This study aims to: (1) khow the design of blended learning development based on dynamic intellectual learning, (2) to know the effectiveness of the use of blended learning based on dynamic intellectual learning on Biology class X add semester in MA Mambaul Ulum. The type of this research is development research using ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. Data collection is done by using document recording, questiononnaires,   and tests. The instruments of data collection used are document recording, questionnaire sheet, and multiple choice type objective test. Data analysis used is descriptive analusis of quolitative, quantitative descriptive, and inferential statistic (t-test). This means that blended learning proved to be effective can significantly improve Biology learning outcomes, so it is advisable to other researchers to develop semilar blended learning or other media that is more interesting as a learning media for students on Biology subjects and other subjects.